2018
DOI: 10.1371/journal.pone.0202738
|View full text |Cite
|
Sign up to set email alerts
|

Circulating osteogenic proteins are associated with coronary artery calcification and increase after myocardial infarction

Abstract: BackgroundCoronary artery calcification (CAC) and atherosclerotic inflammation associate with increased risk of myocardial infarction (MI). Vascular calcification is regulated by osteogenic proteins (OPs). It is unknown whether an association exists between CAC and plasma OPs and if they are affected by atherothrombotic inflammation. We tested the association of osteogenic and inflammatory proteins with CAC and assessed these biomarkers after MI.MethodsCirculating OPs (osteoprotegerin, RANKL, fetuin-A, Matrix … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 52 publications
(54 reference statements)
0
14
0
1
Order By: Relevance
“…In a prospective study of 130 patients, Pessaro et al showed that elevated RANKL levels were associated with CHD (OR 1.75 (95% CI 1.04-2.94, P � 0.035) [75]. Recently, Choe et al analyzed genetic variations using SNPs representative of OPG (rs2073618), RANK (rs1805034), and RANKL (rs2073618) and investigated the association with atherosclerotic plaque instability assessed by cardiac catheterization.…”
Section: Fetuin-a (F-a)mentioning
confidence: 99%
“…In a prospective study of 130 patients, Pessaro et al showed that elevated RANKL levels were associated with CHD (OR 1.75 (95% CI 1.04-2.94, P � 0.035) [75]. Recently, Choe et al analyzed genetic variations using SNPs representative of OPG (rs2073618), RANK (rs1805034), and RANKL (rs2073618) and investigated the association with atherosclerotic plaque instability assessed by cardiac catheterization.…”
Section: Fetuin-a (F-a)mentioning
confidence: 99%
“…6,[48][49][50][51] Vitamin K-Dependent Biomarkers Circulating levels of vitamin K-dependent g-carboxylated MGP and GRP are inversely correlated with vascular calcification. 52,53 Plasma-undercarboxylated MGP and GRP could be potential markers for vascular calcification risk. 9 Low levels of carboxylated and phosphorylated MGP are associated with vascular calcification.…”
Section: Vascular Calcification Markersmentioning
confidence: 99%
“…51,58 An imbalance in the osteoprotegerin/RANKL signaling pathway favors calcification, and thus, it could be used as a marker of vascular calcification. 48,50,53 Pyrophosphate acts by direct physicochemical inhibition of calcium phosphate precipitation and prevents hydroxyapatite formation. 60,61 Circulating inorganic pyrophosphate in blood plasma is negatively associated with calcification; thus, it serves as an endogenous inhibitor of hydroxyapatite formation.…”
Section: Vitamin K-independent Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Some studies have confirmed the involvement of the OPG/RANKL/RANK axis in modulating the inherent and acquired immune responses elaborated in myocardial damage. These studies have shown the involvement OPG/RANKL/RANK axis through its circulatory serum 1819,20 as well as gene expression 19 levels. However, such findings have shown contradictory results yet not solved in the clinical utility of the OPG/RANKL/RANK inflammatory pathway in UA patients.…”
Section: Introductionmentioning
confidence: 97%